2008
DOI: 10.1073/pnas.0810100105
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inactivation of MLL3 histone H3–Lys-4 methyltransferase activity in the mouse reveals vital roles for MLL3 in adipogenesis

Abstract: peroxisome proliferator-activated receptor ␥ ͉ transcription ͉ activating signal cointegrator-2 ͉ coactivator ͉ ASCOM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
188
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(205 citation statements)
references
References 42 publications
(94 reference statements)
16
188
1
Order By: Relevance
“…104 We have observed that the promoters of key adipogenic genes, such as the hormone apm1, present significant levels of H3K4me2 in preadipocytes, when these genes are not expressed. Moreover, this signal coincides with significant loading of RNA Pol II at the same regions, suggesting that this mark is related to developmentally poised chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…104 We have observed that the promoters of key adipogenic genes, such as the hormone apm1, present significant levels of H3K4me2 in preadipocytes, when these genes are not expressed. Moreover, this signal coincides with significant loading of RNA Pol II at the same regions, suggesting that this mark is related to developmentally poised chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Our recently established MLL3 ⌬/⌬ mice showed not only the aforementioned 3 phenotypes (stunted growth, decreased cellular doubling rate, and lower fertility) shared by isogenic ASC-2 ϩ/Ϫ mice (15), but also 2 additional phenotypes. First, all MLL3 ⌬/⌬ mice had very little white fat, which led us to identify crucial roles for ASCOM in adipogenesis (19). Second, within 4 months after birth, Ϸ50% of MLL3 ⌬/⌬ mice displayed unusual hyperproliferation and tumors in the innermost layer of ureter cells (i.e., urothelial cells) located close to the renal pelvis ( Fig.…”
Section: Targeted Inactivation Of Mll3 H3k4 Methyltransferase Activitmentioning
confidence: 99%
“…Discussion ASC-2, a coactivator with potential links to cancer (16)(17)(18), resides in a steady-state complex, ASCOM, that contains the H3K4 methyltransferase MLL3 or its paralogue MLL4 (7,8). To establish potentially interrelated functions of ASC2 and MLL3/4, we have used a variety of in vitro and in vivo assays (8,19,30). Interestingly, our recent analysis of a homozygous mouse line that expresses an enzymatically inactivated mutant form of MLL3 demonstrated genetic interactions between ASC-2 and MLL3 (8,15).…”
Section: Targeted Inactivation Of Mll3 H3k4 Methyltransferase Activitmentioning
confidence: 99%
“…Thus, both MLL and MLL5 have been implicated in the regulation of hematopoiesis, indicating that a common molecular mechanism might be used by these two Trithorax proteins. It has been shown that MLL3 plays a vital role in adipogenesis (14,15), whereas MLL4/WBP7 (also known as MLL2) is essential for mouse embryonic development (16), proper embryonic stem cell differentiation (17), and macrophage activation (18). The precise roles of MLL2/ALR, SET1A, and SET1B in embryonic development or hematopoiesis remain to be determined.…”
mentioning
confidence: 99%